Spontaneous rupture of a uterine leiomyoma accompanied by a hematoma appearing as a cystic lesion on imaging: A case report - Satoshi Suzuki, MD; Akira Kunimatsu, MD, PhD; Taku Tajima, MD, PhD; Shu Suzuki, MD; Yoko Nagayoshi, MD, PhD; Yuichiro Hayashi, MD; Shinsuke Aida, MD, PhD; Shigeru Kiryu, MD, PhD (Radiology Case Reports, 2024)
The rupture of a uterine leiomyoma is a rare complication. We report a case of ruptured leiomyoma that formed a hematoma that was initially suggestive of an ovarian origin. Magnetic resonance imaging revealed intact ovaries and a cystic lesion adjacent to leiomyomas. During surgery, the cystic lesion was found to be a hematoma caused by a rupture of the leiomyoma.